Study Interpretation Phenomenon Magnetostriction and Noise of Lamination FeSi Sheets for Transformer - Mukhamad Aziz; Vincent Lanfranchi; Nicolas Buiron (IPTEK Journal of Proceedings Series, 2015)
One of the main problems using a transformer is the vibration and noise. This phenomenon occurs due to deformation/ magnetostriction of lamination sheets transformer core. In this research, the analysis of difference the hysteresis curve, noise and magnetostriction between the rolling direction & the transverse direction have been done. Magnetostriction was measured by gauge of deformation. Acoustic noise was measured by microphone. Magnetic saturation of the rolling direction was higher than in the transverse direction. In contrast, the magnetostriction & acoustic noise of transverse direction was higher than the rolling direction. Harmonic frequency noise measurement had similarities with harmonic frequency magnetostriction: 100, 200, 300, 400 Hz. With increasing current/voltage, the amplitude of the harmonic frequencies noise and magnetostriction will increase.